Kesetaraan Gender dan Representasi Politik: Perjuangan Partisipasi Perempuan dalam Politik di Kabupaten Nagan Raya, Aceh - ningsih, Firda; Melayu, Hasnul Arifin; Eriyanti , Nahara (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
Article 2 of Law Number 7 of 2008 concerning Political Parties jo. Article 173 Paragraph 2 of Law Number 7 of 2018 concerning General Elections mandates that political parties must include at least 30% women in their management and establishment; however, the practice of this target is not being met. The problem of this research focuses on the low participation of women in politics, both according to positive law and Islamic law, as well as the involvement of women in politics in the Nagan Raya DPRK through a fiqh siyasah analysis. This study aims to identify the level of women's political participation from the perspective of law and Islamic law and to explore the factors influencing women's political involvement in Nagan Raya. The research uses a qualitative descriptive method with a statutory approach and descriptive analysis. The research findings indicate that women's participation and position in politics are critical to the effectiveness of their role in policy formulation and decision-making within public institutions. The lack of women's participation in politics is due to the deeply ingrained patriarchal culture in society, which results in gender inequality between men and women. Women's representation in parliament to advocate for their rights and interests in decision-making or policy formulation remains very low. The contribution of this research is to provide insights into the importance of women's involvement in politics and its impact on creating more inclusive policies. This study also highlights the need to address social and cultural barriers to increasing women's political participation in Indonesia. .